DETERMINATION OF THE BEARING CAPACITY OF FLEXIBLE REINFORCED CONCRETE BEAMS OF RECTANGULAR SECTION WITH A ONE-SIDED COMPRESSION FLANGE ON THE BOUNDARY CONDITIONS OF CONCRETE AND REINFORCEMENT - SOBIROVA. D.T; MILLADJONOVA .Z.R (International Journal of Innovations in Engineering Research and Technology, 2021)
The development of a production base in residential, civil and industrial construction, as well as in many engineering structures, is important with the use of simple and prestressed reinforced concrete structures. Improving the quality and reducing the specific weight of reinforced concrete structures has always been an urgent problem. The solution to this problem is solved through the use of effective reinforced concrete structures, namely high-strength concrete, high-strength reinforcement, lightweight aggregates and similar factors. In construction practice, the use of simple and prestressed reinforced concrete structures with modified design solutions requires clarification and addition of calculation methods, as well as an in-depth study of cases of stresses and deformations of reinforced concrete elements. Cross-sectional shapes have a large influence on the stresses and strains of flexible reinforced concrete elements during use, preparation and restoration. Taking into account the influence of cross-sectional dimensions on the stress and strain state is one of the most important issues today.